(untitled) (Global Journals of Research in Engineering, 2024)
Ing s The study of Science Technology and Society STS is quite embracing and relevant to today s society In this article we intend to approach the issue and reflect on the interaction that exists between the three areas and education as well as the relationship with Science Technology Engineering and Mathematics STEM For that a qualitative research was carried out from a narrative review about the subject in books articles and works presented in event annals highlighting STS in the context of education the challenges faced in relation to the STEM approach and the possibilities of integration between science technology and society in engineering courses The results indicate that there are challenges such as lack of adequate training for teachers lack of didactic resources and resistance to change on the part of some educators and managers as well as that the STS approach in education and STEM in the training of engineers makes it possible to develop professional skills and competencies focused on sustainability innovation and a fairer and more humane society